(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article explores the role of mobile learning (m-learning) in English language education within higher education systems, focusing on both its pedagogical opportunities and associated challenges. Drawing on constructivist and sociocultural learning theories, the study examines how mobile technologies facilitate flexible, personalized, and context-aware language learning experiences. Particular attention is given to the ways mobile devices enhance learner autonomy, motivation, and engagement through access to authentic materials, real-time communication, and interactive applications. The article also analyzes the impact of mobile learning on the development of key language skills, including listening, speaking, reading, and writing, emphasizing its potential to support continuous and informal learning beyond traditional classroom settings. At the same time, the study critically addresses the limitations of mobile learning